تصنيف المحافظات السورية حسب الإنفاق الاستهلاكي للأسرة باستخدام التحليل العنقودي - أحمد طالب (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة لمعرفة الاختلاف في قيم الإنفاق الاستهلاكي للأسرة بين المحافظات السورية , بالإضافة إلى تحديد أيً من مكونات وبنود الإنفاق المختلفة التي ساهمت بدرجة كبيرة لحدوث هذا الاختلاف والتفاوت بين المحافظات , حيث تم استخدام أسلوب التحليل العنقودي لمعرفة هذا الاختلاف والتصنيف . وكانت أهم النتائج التي تم التوصل إليها : ظهرت ثلاثة مجموعات للمحافظات السورية هي حصيلة عملية التحليل العنقودي , حيث تضمنت المجموعة الأولى المحافظات ذات الإنفاق الاستهلاكي العالي ، وشملت محافظة دمشق , وتضمنت المجموعة الثانية المحافظات ذات الإنفاق الاستهلاكي المتوسط وشملت محافظات ريف دمشق , حمص , طرطوس , اللاذقية , السويداء , درعا , القنيطرة . وتضمنت المجموعة الثالثة المحافظات ذات الإنفاق الاستهلاكي المنخفض ، وشملت محافظات حماة , إدلب , حلب , الرقة , دير الزور , الحسكة . كما تبين أن أهم مكونات ومتغيرات الإنفاق الاستهلاكي التي ساهمت في تصنيف المحافظات السورية لمجموعات متجانسة هي الإنفاق على السكن , الإنفاق على التعليم , الإنفاق على الصحة , الإنفاق على النقل والاتصالات . This study aims to determine the difference of householder spending values between the Syrian provinces. It also aims to find out which of the components and the various items of expenditure, that contributed significantly to the occurrence of this difference and disparity between provinces , where cluster analysis method was used to find out this difference and classification . The most important results that have been reached: The result of cluster analysis is that there are three groups of Syrian provinces , the first group included the provinces of high householder spending such as Damascus province , the second group included the provinces of medium householder spending such as: Rural Damascus , Homs , Tartus , Lattakia , Al-Sweida , Daraa , Al – Quneitra . The third group included the provinces of low householder spending such as: Hama , Idleb , Aleppo , Al-Rakka , Deir-ez-Zor , Al-Hasakeh . Accordingly , that most important components and variables of householder spending, which contributed to the classification of the Syrian provinces of homogeneous groups are spending on housing , spending on education , spending on health , spending on transport and communications .